2021
DOI: 10.3390/ma14051291
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity and Viscosity: Review and Optimization of Effects of Nanoparticles

Abstract: This review was focused on expressing the effects of base liquid, temperature, possible surfactant, concentration and characteristics of nanoparticles including size, shape and material on thermal conductivity and viscosity of nanofluids. An increase in nanoparticle concentration can lead to an increase in thermal conductivity and viscosity and an increase in nanoparticle size, can increase or decrease thermal conductivity, while an increase in nanoparticle size decreases the viscosity of the nanofluid. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(39 citation statements)
references
References 100 publications
(370 reference statements)
0
39
0
Order By: Relevance
“…As results, the anatase-water nanofluid has higher heat transfer coefficient. As the uniformity of the nanoparticles in the base liquid increases, the possibility of nanoparticle-nanoparticle and nanoparticle-molecule collisions and interactions increase and as a result, the energy transportation across the working fluid increases and consequently would increase the thermal conductivity [8,38] and heat transfer coefficient. Rutile TiO 2 nanoparticles were used to enhance the efficiency of dye-sensitized and perovskite solar cells which can be seen in references [42,43,[48][49][50][51][52][53][54][55][56].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As results, the anatase-water nanofluid has higher heat transfer coefficient. As the uniformity of the nanoparticles in the base liquid increases, the possibility of nanoparticle-nanoparticle and nanoparticle-molecule collisions and interactions increase and as a result, the energy transportation across the working fluid increases and consequently would increase the thermal conductivity [8,38] and heat transfer coefficient. Rutile TiO 2 nanoparticles were used to enhance the efficiency of dye-sensitized and perovskite solar cells which can be seen in references [42,43,[48][49][50][51][52][53][54][55][56].…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing the nanoparticle size may decrease or increase the nanofluid thermal conductivity, however it was observed that in most cases, nanofluid thermal conductivity [ 8 , 38 ] and nanofluid viscosity [ 39 ] increase with decreasing nanoparticle size. It was observed that the heat transfer coefficient increases with increasing thermal conductivity and decreases with increasing viscosity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of nanoparticles to high-Prandtl number liquids significantly increases the heat transfer performance of micro heat-sinks [ 5 ]. An increase in nanoparticle concentration can lead to an increase in thermal conductivity and viscosity and an increase in nanoparticle size [ 6 ]. Nanofluids contribute to the improvement of heat transfer processes and reduce and optimize thermal systems.…”
Section: Introductionmentioning
confidence: 99%